Proceedings of the 2004 IEEE International Conference on Control Applications, 2004.
DOI: 10.1109/cca.2004.1387196
|View full text |Cite
|
Sign up to set email alerts
|

Time localisation of surface defects on optical discs

Abstract: Abstract-Many have experienced problems with their Compact Disc player when a disc with a scratch or a finger print is tried played. One way to improve the playability of discs with such a defect, is to locate the defect in time and then handle it in a special way. As a consequence this time localisation is needed to be as good as possible. Fang's algorithm for segmentation of the time axis is used since it has good performance in an application like this. Fang's algorithm has a clear potential for time locali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 4 publications
1
9
0
Order By: Relevance
“…Other reasons for fast common channel parameter variations are: dust, fingerprints, scratches on the disc, dropouts, etc. [20], [22]. These observations lend support to the assumed parameter model, not just for TwoDOS but also for other 2-D storage systems.…”
Section: Minimum-latency Adaptationsupporting
confidence: 52%
“…Other reasons for fast common channel parameter variations are: dust, fingerprints, scratches on the disc, dropouts, etc. [20], [22]. These observations lend support to the assumed parameter model, not just for TwoDOS but also for other 2-D storage systems.…”
Section: Minimum-latency Adaptationsupporting
confidence: 52%
“…The results using the new residuals show an improvement by 6 samples in the beginning and 3 samples in the end. In [26] an extention of the threshold method used on the new residuals is presented, using this method results in an avarage improvement of the fault localization of 6-8 samples in both the begining and the end of the fault. This improvement can seem less significant compared to duration of the scratch which is 441 samples, but many practical experiments with fault tolerant control in CD players have shown that an improvement of a few samples of the fault detection means a lot in the achieved controller performance.…”
Section: Discussion On the Estimated Signalsmentioning
confidence: 97%
“…The intersection between this tangent plane and is consequently an approximation of (26). Finding the intersection, gives a and at a given iteration this gives an update in which is denoted This approximation can again be used as a starting point for a new tangent plane and a new intersection is computed.…”
Section: A the Scaling Projection Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…From the focus and radial residuals, α f [n] and α r [n], faults are extracted based on the algorithm described in (Odgaard and Wickerhauser 2004). From a large number of CDs, with scratches, sequences with detected scratches are extracted into a column vector with the length of 256=2 8 samples.…”
Section: Training Datamentioning
confidence: 99%